Civic Engagement Perusahaan di Masa Pandemi Covid-19 : CSR Bank Mandiri untuk RS Jantung dan Pembuluh Darah Harapan Kita - Ira Kumala Sari; Bambang Shergi Laksmono (Esensi: Jurnal Bisnis dan Manajemen, 2022)
AbstractThe study in this research focuses on describing civic engagement or the involvement of citizens from the business world on government policies in handling Covid-19 in the form of CSR programs. The theme was raised based on the importance of their involvement in the realization of government policies related to handling Covid-19. An important level in this research is Bank Mandiri's civic engagement in the Covid-19 CSR program at the RSJPDHK. The role of civic engagement is necessary apart from being an obligation of every citizen as well as the success of a program. This research method uses a qualitative approach with a descriptive type of research. The informant selection technique in this study used non-probability sampling. The results of the research show that Bank Mandiri has implemented civic engagement in the form of CSR Covid-19 in the Non-Program CSR category of Bank Mandiri during the Covid-19 pandemic, only from the point of view of civic engagement it has not fully met the objectives of civic engagement because the CSR provided is not sustainable. .